Affective and Physiological Responses During Acute Pain in Virtual Reality: The Effect of First-Person Versus Third-Person Perspective - Turbyne, Collin; de Koning, Pelle; Smit, Dirk; Denys, Damiaan (Frontiers in Virtual Reality, 2021)
Background: Virtual reality (VR) has been previously shown as a means to mitigate acute pain. The critical parameters involved in the clinical efficacy of mitigating acute pain from different perspectives remains unknown. This study attempted to further deconstruct the critical parameters involved in mitigating acute pain by investigating whether affective and physiological responses to painful stimuli differed between a first and a third person perspective in virtual reality. Methods: Two conditions were compared in a repeated-measures within subject study design for 17 healthy participants: First person perspective (i.e. where participants experienced their bodies from an anatomical and egocentric perspective) and third person perspective (i.e. where participants experienced their bodies from an anatomical perspective from across the room). The participants received noxious electrical stimulation at pseudorandom intervals and anatomical locations during both conditions. Physiological stress responses were measured by means of electrocardiography (ECG) and impedance cardiography (ICG). Subjective scores measuring tension, pain, anger, and fear were reported after every block sequence. Results: There were no significant differences in physiological stress responses between conditions. However, the participants reported significantly higher tension during the third person condition. Conclusion: Relative to a third person perspective, there are no distinct physiological benefits to inducing a first person perspective to mitigate physiological stress responses to acute pain in healthy individuals. However, there may be additional clinical benefits for doing so in specific clinical populations that have shown to benefit from relaxation techniques. Further research is needed in order to refine the clinical utility of different perspectives during virtual reality immersions that serve to act as a non-pharmacological analgesic during acute pain.